Implementasi Metode Ruqyah Melalui Terapi Air: Kasus Buya Zaharuddin, Simpang Sungai Rengas, Batanghari - Dina Muhibbah (JIGC (Journal of Islamic Guidance and Counseling), 2022)
Abstract: This study aims to find out how the implementation of the ruqyah method through water therapy, the problems faced, and the positive impact carried out by Buya Zaharuddin at Sungai Rengas Intersection, Batanghari. This research is a field research where the data is obtained through interviews and observations. This study concluded that the implementation of the ruqyah method through water therapy carried out by Buya Zaharuddin included performing ablution, preparing water, reading certain verses, spitting a little into the water, giving the patient a drink, and bathing the patient with lime and young coconut shoots. durian leaves. One of the problems faced in implementing the ruqyah method through water therapy is the problem that arises from the attitude of the patient who shows resistance when he wants to do ruqyah. The positive impact of implementing the ruqyah method through water therapy for ruqyah experts, patients and families of ruqyah patients, among others, can divert themselves from shirk, get peace of mind, get treatment carrying grace and improve relationships with the environment.